Reduction of inflammation and improvement of skin tissue repair using biomaterials composed of hydroxyapatite and chitosan associated to conditioned media derived from dental pulp stem cells - Vidotti, R. B. [UNESP]; Yoshikawa, A. H.; Sant'Ana, M.; Souza, H. R.; Possebon, L.; Navarro da Rocha, D.; Ferreira, J. R.M.; Vidotti, G. A.G.; Girol, A. P. [UNESP] (Elsevier, 2025)
Introduction: Inflammatory skin diseases, including dermatitis, are characterized by uncontrolled inflammatory responses that affect approximately 20 % of the global population. Recent therapies primarily focus on inhibition rather than regulating abnormal inflammatory response, which can induce a series of secondary side effects and drug resistance in long-term treatment. In this context, advanced therapy products based on mesenchymal stem cells are promising due to their influence on tissue regeneration. Objectives: To evaluate skin healing in rats induced to manifest dermatitis and treated with biomaterial composed of hydroxyapatite and chitosan associated or not with conditioned medium from stem cells from the dental pulp. Methods: One of the primary models to investigate mechanisms of dermatitis involves the application of acetone followed by water. Skin injury was induced on the backs of the animals by rubbing acetone for 5 min for three consecutive days under sedation followed by water. The treatments started on day 3 and lasted 5 days. The experimental groups (n = 5/group) were: induced without treatment (G1), induced and treated with 10 % hydrocortisone ointment (standard treatment, 1×/day) (G2), induced and treated with biomaterial without conditioned medium (G3) and with conditioned medium (G4), applied once as a dressing. On the 8th day post-induction, the animals were euthanized to collect blood and skin fragments for histopathological and immunohistochemical studies and dosages of chemical mediators. Results: Groups G1 and G2 showed rupture and hyperplasia of the epidermis and inflammatory influx. Group G1 presented the highest number of mast cells, mainly degranulated ones. Groups G3 and G4 showed less thickened skin, a better tissue regeneration process, and reduced mast cells. Plasma histamine levels were also reduced in the G4 group. The expression of annexin A1 (AnxA1) and positive cells for Janus kinase (JAK)-1 and JAK-3 presented increased in groups G1 and G2 but reduced in the groups treated with biomaterials, mainly G4. Likewise, the treatments in G3 and G4 lowered levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and vascular endothelial growth factor (VEGF). Conclusion: Treatments with biomaterials especially associated with the conditioned medium reduced the inflammatory process and promoted tissue regeneration in the dermatitis model, demonstrating potential therapeutic application.
Keywords: Inflammatory mediators; Mesenchymal stem cells; Skin healing